Onset latency of segmental dystonia after deep brain stimulation cessation: A randomized, double‐blind crossover trial. Issue 7 (20th December 2013) - Levin, Johannes; Singh, Arun; Feddersen, Berend; Mehrkens, Jan‐Hinnerk; Bötzel, Kai
ABSTRACT Background Deep brain stimulation (DBS) of the globus pallidus internus is an effective treatment for cervical dystonia (CD). Interestingly, the onset of initial DBS effects is significantly prolonged compared with that in other diseases, such as Parkinson's disease. The return of symptoms after cessation of DBS could be delayed as well, but this has not been studied systematically. Methods In patients who were treated for CD using DBS and had a good treatment effect, we compared interruption of DBS with sham‐OFF in a randomized, double‐blind crossover trial. Results We observed that dystonic features appeared within a few minutes at almost full intensity in all patients after the cessation of DBS. Conclusions The almost immediate onset of dystonic features in our sample seems to exclude mechanisms with long time constants from the pathophysiology of dystonia. Thus, it is likely that, in these patients, an aberrant pattern of neural activity representing an inappropriate set point value for the position of the head is responsible for dystonia. © 2013 International Parkinson and Movement Disorder Society